Environmental quality and macroeconomic phenomenon - S. Amar; A. Satrianto; A. Ariusni; A. Ikhsan; E.S. Siregar (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aimed to analyze the influence of economic growth, industrialization, government spending, and environmental taxes on environmental quality as well as the influence of environmental quality, unemployment, and inflation on Indonesia’s economic growth. This condition is important to maintain environmentally friendly economic development to achieve sustainable development.METHODS: The study was conducted using simultaneous equation model analysis considering classical assumption tests such as normality tests, granger causality and heteroscedasticity. This study data began in 2015 to 2021 in 34 provinces in Indonesia. In this study, the determinants of environmental quality used were industrialization, government spending and environmental taxes, whereas those of economic growth were unemployment and inflation.FINDINGS: The results of the study indicate that economic growth, industrialization, government spending and environmental taxes have a significant effect on Indonesia’s environmental quality. Collectively, these determinants account for 22.18 percent of the variance. However, environmental quality and unemployment do not have a significant effect on Indonesia’s economic growth. Meanwhile, inflation has a significant effect on economic growth. Simultaneously, the influence of the determinants of economic growth is 33.52 percent.CONCLUSION: Economic growth, industrialization, government spending and environmental taxes have a significant influence on Indonesia’s environmental quality. On the other hand, environmental quality and unemployment do not have a significant effect on Indonesia’s economic growth. Meanwhile, inflation has a significant effect on economic growth. The policies suggested, include the following 1) the government must be able to maintain environmental quality while still encouraging economic growth, implemented by creating an environmentally sound growth concept or applying the green economic concept to harmonize growth and the environment; 2) the industrialization process must be maintained so that it does not damage the environment, and pollution threshold rules created in the industrialization process must be applied